Faktor Yang Berhubungan Dengan Personal Hygiene Pada Remaja Putri SMP Negeri 4 Majene - hijrah, muh fauzar; muzakkir; Husaeni, Hermin; Muzdalia, Ika (Journal of Health Education and Literacy, 2020)
Personal hygiene is an action to maintain the cleanliness and health of a person for his welfare, both physical and psychological. If someone is sick, usually the health problem is less attention. This happens because it considers the problem of cleanliness is a trivial problem, even though if it is not paid attention to can affect general health. This study aims to determine the factors associated with personal hygiene in young women at SMP Negeri 4 Majene. This study used an analytic survey design with a cross sectional study approach. This research was conducted at SMP Negeri 4 Majene, Majene Regency with a total sample of 47 young women. Sampling is done by total sampling method. The results showed sufficient personal hygiene behavior of 31 people (65.1%) and less by 16 people (34.9%). Chi-Square test results showed no relationship between the level of knowledge of young women with personal hygiene with Fisher Exact values ​​obtained p = 1.00 and there was no relationship between the level of confidence of young women with personal hygiene with continuity correction values ​​obtained p = 0.533. The conclusion of this study is that there is no relationship between the factors of knowledge and belief in personal hygiene of teenage girls at Majene Neg 4 Middle School.